Jawabanmu

2014-03-21T23:32:39+07:00
Un = a + (n-1)b
U5 = a + (5-1)b = a + 4b
U7 = a + (7-1)b = a + 6b
a+4b+a+6b = -42
2a + 10b = -42
U10 =  a + (10-1)b = a + 9b = -41
bisa dijadikan 2a + 18b = -82
2a+10b = -42
2a-2a habis.. 18b-10b = 8b... -82-(-42) = -40
8b = -40, b = -5
dimasukin ke rumus 2a+10b = -42, jadi a = 4
Un = 4 + (n-1)-5
Un = 4+ -5n + 5
Un = -5n + 9
2014-03-21T23:42:47+07:00
U5+U7 = -42
a+4b+a+6b = -42
2a+10b =-42
a+ 5b = -21 (U6)
hasil kurangi dai U10-U6 ...b= -5
U6=a +(5) -5
-21 = a+(-25)
a = 4
Sehingga rumus Un = 4 +(n-1) -5
1 5 1